DESIGN AND DEVELOPMENT OF STAFFING INFORMATION SYSTEM AT PT BAKRI KARYA SARANA BATAM - Desi Pibriana; Oxana Olivia Tanga (Jurnal TAM (Technology Acceptance Model), 2019)
Nowdays, information technology has been applied to all sectors in human life and has been used in various fields to support a business processes in order to run faster, accurately and efficiently. PT Bakri Karya Sarana is a company that is engaged in cleaning service provider or outsourcing employee provider that has 470 outsourcing employee in Batam area. In its employee data management, PT Bakri Karya Sarana still has several obstacles in recruiting new prospective employees, registering employee’s attendance, permission, leave, mutation, promotion, demotion, resignation, warning letters, field staff appraisal and employee quality assessment by clients. The purpose of this study is to build a website-based of Staffing Information System at PT Baki Karya Sarana to simplify and minimized the problems happened in Human Resource Development (HRD) division. Framework for the Application of System thinking (FAST) is a methodology of this study. This Staffing Information System was built using notepad++, PHP as a programming language and MySQL as data storage media. This Staffing Information System can assist HRD Division in managing all staffing data, starting from recruiting new prospective employees, performance data collection process and empoyee’s rights until the process of reporting can be done faster and accurately.